Efektivitas Alat Tangkap Mini Purse Seine Menggunakan Sumber Cahaya Berbeda Terhadap Hasil Tangkap Ikan Kembung (Rastrelliger sp.) [Fishing Tool Effectivity of Mini Purse Seine by Using Different Light Source for Catching Fish of Puffer Fish (Rastrelliger sp.) ] - Akhmad Farid; Wahyu Andy Nugraha; Ifa Nur Rosyidah (Faculty of Fisheries and Marine Universitas Airlangga, 2011)
AbstractIn fish catching activity, the fishermen in Banyuanyar district use mini tools for catching fish (purse seine) and use light assist tools for an operation in the night day. The light, that is used, is kerosene pressure lantern and mercury lights or lamp that is used on water surface (surface lamp). This kind of light is used to collect